2010
DOI: 10.1213/ane.0b013e3181c04faf
|View full text |Cite
|
Sign up to set email alerts
|

Gestation-Related Reduction in Lumbar Cerebrospinal Fluid Volume and Dural Sac Surface Area

Abstract: These findings indicate an association between gestational week (Weeks 31-39) and a reduction in both CSF volume and dural sac surface area. These reductions may, at least in part, explain the facilitation of the spread of intrathecal anesthesia in pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…Onuki et al have suggested that during the third trimester of gestation a decrease in lumbosacral CSF volume may be observed. 6 Silverberg et al have reported a decreased production rate in dementia of the Alzheimer's type. 7 Dry lumbar punctures have also been reported in cases with an epidural abscess.…”
Section: Resultsmentioning
confidence: 99%
“…Onuki et al have suggested that during the third trimester of gestation a decrease in lumbosacral CSF volume may be observed. 6 Silverberg et al have reported a decreased production rate in dementia of the Alzheimer's type. 7 Dry lumbar punctures have also been reported in cases with an epidural abscess.…”
Section: Resultsmentioning
confidence: 99%
“…17 Recently, magnetic resonance imaging (MRI) has shown a significantly reduced mean CSF volume and dural sac surface area in pregnant subjects. 18 Non-mechanical factors, such as an increase in progesterone concentration during pregnancy, may alter the susceptibility of nerves to local anesthetics during pregnancy. 19 Mechanisms which may be involved include direct effects on membrane excitability, indirect actions on neurotransmitters, increased permeability of the neural sheath and potentiation of the analgesic effect of endogenous opioids.…”
Section: Discussionmentioning
confidence: 99%
“…5 Epidural blood vessels become engorged during the third trimester of pregnancy, resulting in a reduction in both CSF volume and dural sac surface area. 6 This may explain the increased sensory level achieved by neuraxial anesthesia in pregnancy. 6 Focal etiologies of increased intracranial pressure…”
Section: Physiological Changes During Pregnancy and Relationship To Imentioning
confidence: 99%
“…6 This may explain the increased sensory level achieved by neuraxial anesthesia in pregnancy. 6 Focal etiologies of increased intracranial pressure…”
Section: Physiological Changes During Pregnancy and Relationship To Imentioning
confidence: 99%